Analysis of Acceptance Factors of Pospay Application Users in Surabaya City Using Modified TAM - Ni Made Berliana; Anita Wulansari; Virdha Rahma Aulia (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2025)
This study aims to analyze the factors that influence user acceptance of the Pospay application in Surabaya by using a modified Technology Acceptance Model (TAM). Pospay is a digital platform owned by PT Pos Indonesia that offers financial transaction services. Although the app has been downloaded over 5 million times, it still faces acceptance issues, as reflected by the high number of negative reviews due to system errors, verification failures, and unstable performance. To address these challenges, the TAM model was extended by incorporating variables such as Facilitating Conditions, Lifestyle Compatibility, Quality of Internet Connection, Perceived Security, Perceived Trust, Perceived Risk, Self-Efficacy, and Satisfaction. Data were collected from 523 active users and analyzed using Structural Equation Modeling–Partial Least Squares (SEM–PLS). The results showed that Facilitating Conditions, Perceived Ease of Use, and Perceived Usefulness significantly influence Attitude. Furthermore, Perceived Ease of Use, Perceived Usefulness, Perceived Security, Self-Efficacy, and Satisfaction have a significant effect on Intention to Use. Meanwhile, variables such as Attitude, Lifestyle Compatibility, Quality of Internet Connection, Perceived Trust, and Perceived Risk did not significantly affect Intention to Use. These findings highlight the importance of improving usability, usefulness, security, satisfaction, and user confidence to enhance the acceptance and usage of the Pospay application more effectively.